OVERVIEW OF THE DEVELOPMENT OF WORLD RELIGIONS AND THE HISTORY OF THEIR SPREAD IN THE NUSANTARA - Yogi Prihantoro; Peni Nurdiana Hestiningrum (Widya Agape School of Theology and Indonesia Christian Theologians Association, 2020)
Whether the entry of world religions into Indonesia is driven more by puritanical economic, political, or missiological (da'wah) motives, has colored the uniqueness of each, and has influenced the thickness or thinness of tolerance levels towards the presence of